1986
DOI: 10.2527/jas1986.631121x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Amino Acid Complexes for Swine

Abstract: Two experiments were conducted to determine the effect of sources of dietary zinc on gain, feed conversion and blood and bone traits of swine. In the first experiment 96 pigs were used in a 28-d study. The pigs were fed diets with no supplemental Zn or with either 9 or 12 ppm supplemental Zn from zinc sulfate (ZnSO 4), zinc methionine (ZnMet) or zinc methionine with picolinic acid (ZnMet w/PAL each with or without 5% added corn oil. There were differences (P<.05) in average daily gain (ADG) and average daily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
0
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 11 publications
9
39
0
5
Order By: Relevance
“…Similar results were previously reported by Hill et al [10]. In contrast, an improved growth rate of the piglets of similar live weight was observed by Adeola et al [1] by adding 100 mg·kg -1 of Zn in a corn-soybean meal diet containing 23 mg·kg -1 of Zn.…”
Section: Zn Balancesupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were previously reported by Hill et al [10]. In contrast, an improved growth rate of the piglets of similar live weight was observed by Adeola et al [1] by adding 100 mg·kg -1 of Zn in a corn-soybean meal diet containing 23 mg·kg -1 of Zn.…”
Section: Zn Balancesupporting
confidence: 90%
“…In pigs, similar observations are reported in the literature with diets containing Zn levels below the requirements [10,34,36] as well as with diets containing pharmacological Zn levels [9,31]. In chicks, inconsistent results were published.…”
Section: Bioavailability Of Zn Sourcessupporting
confidence: 63%
See 1 more Smart Citation
“…Bone Zn content is a reliable indicator for Zn bioavailability as it is highly correlated with dietary Zn content (Hill et al, 1986;Wedekind et al, 1994;Mohanna and Nys, 1998;Revy et al, 2003) and as it's maxima (plateau) is reached when dietary Zn content is higher than needed for other parameters. When dietary zinc content is increased, the approach of a physiological plateau for bone Zn, most probably explains the negative quadratic effect of supplemented Zn observed in broilers (ZN I 3 ZN I , P , 0.001 in Analysis II) and in piglets (ZN I 3 ZN I , P , 0.05 in Analysis II) and the negative interaction between supplemented Zn and supplemented phytases observed in broilers (ZN I 3 Phytase S , P , 0.05 in Analysis II).…”
Section: Description Of the Databasesmentioning
confidence: 99%
“…On the other hand, Apgar et al (1994) did not verify any response of this combination in growth. Hill et al (1986) found higher feed intake with the use of zincmethionine, but feed conversion was not influenced when that chelate was combined with copper sulfate. Higher nominal zinc absorption was found by Hill et al (1987) for zinc-methionine as compared to zinc chloride, suggesting differences in transport rates between these two sources.…”
Section: Performance Of Poultry Fed Chelated Mineralsmentioning
confidence: 92%